Lidocaine in Decreasing the Perioperative Opioid Analgesic Requirements After Ambulatory Surgery - Tanwani, Hanesh; Anwar, Muhammad Amim; Bughio, Shehrum; Hussain, Sadam; Kanwal, Nazish; Fatima, Ghulam (Biological and Clinical Sciences Research Journal, 2025)
Infusions of lidocaine at low doses have an excellent safety record. It has been proposed that intravenous lidocaine infusion improved overall surgical outcomes and reduced postoperative discomfort. Objective: To compare the mean opioid analgesic requirements in patients undergoing ambulatory surgery receiving lidocaine versus placebo. Methods: This randomized control trial was conducted from January 2024 to June 2024 at the Anaesthesia Department of Liaquat National Hospital. A total of 80 patients were included and divided equally into the 1.5 mg/kg lidocaine group and the Placebo group. A visual analog scale (VAS) was used to measure pain while at rest. At the time of discharge from the anesthesia care unit (PACU), 2 hours and 4 hours in a hospital stay. The data was compiled and analyzed using SPSS. Results: The placebo group consisted of 45% males, while the lidocaine group comprised 50% male patients. The mean VAS in PACU at 2 and 4 hours for the lidocaine group was 1.50±2.01 and 1.70±1.69 respectively, while the mean VAS for the placebo group was 1.75±1.94 and 3.52±3.04. Overall, 20% of patients in the lidocaine group required nalbuphine, compared to 50% of placebo. The study groups and the need for nalbuphine were significantly associated (p = 0.005). There was a significant mean difference in nalbuphine dose by study group for patients whose surgeries lasted longer than 60 minutes (p = 0.038). Conclusion: Lidocaine infusion reduces the incidence of PONV, the total need for opioids, and the severity of postoperative pain.